2007
DOI: 10.1111/j.1095-8312.2007.00872.x
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal evolution of South American frugivorous butterflies in the Satyroid clade (Nymphalidae: Charaxinae, Morphinae and Satyrinae)

Abstract: We describe the chromosome numbers of a monophyletic group of Satyroid subfamilies of primary fruit-attracted butterflies from South America: Charaxinae, Morphinae (including Brassolini) and Satyrinae. The charaxines do not have a distinct modal number. Their chromosome numbers are in the range n = 6-50, with n = 7-9, n = 12, n = 16, n = 19-21, n = 26, and n = 28-31 being the most common numbers. Within the Morphinae, the Morphini have a modal n = 28 and the Brassolini a modal n = 29, with few exceptions. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
25
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 34 publications
8
25
0
Order By: Relevance
“…Additional evidence that supports the hypothesis herein proposed, comes through the karyotypic studies performed by Brown et al (2007), which demonstrated differences of the chromosomal number between P. lamia (n = 28-30), P. chalybaea (n = 26-30) and P. kesselringi (n = 20). This variability number has a fundamental role in maintaining postzygotic isolation between well-established species (Kandul et al 2004(Kandul et al , 2007Saura 2013).…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Additional evidence that supports the hypothesis herein proposed, comes through the karyotypic studies performed by Brown et al (2007), which demonstrated differences of the chromosomal number between P. lamia (n = 28-30), P. chalybaea (n = 26-30) and P. kesselringi (n = 20). This variability number has a fundamental role in maintaining postzygotic isolation between well-established species (Kandul et al 2004(Kandul et al , 2007Saura 2013).…”
Section: Discussionsupporting
confidence: 74%
“…Paluch et al (2011) pointed out that individuals collected in the Ecological Park João Vasconcelos Sobrinho, Caruaru, Pernambuco, Brazil might constitute a distinct subspecies of P. lamia, however they also did not describe that. In the present study, morphological evidences from androconial patches and female genitalia were founded and its support the Kesselring & Ebert's opinion, in addition to the differences in the chromosomal number on this species (Brown et al 2007 (Figures 21-24, 34, 58-59) Pierella lamia ssp. ; Zacca, Bravo & Araújo, 2011, p. 141 Diagnosis.…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…In particular, we wish to find out whether there is a modal number and if not, which factors drive the diversity. As a reference we use the results obtained for nymphalids (Brown et al 1992, 2004, 2007a, 2007b) and lycaenids, extensively covered in the literature (Robinson 1971; White 1978). The overall aim is to cast light on the relationships and evolution in a cytogenetically little studied butterfly family.…”
mentioning
confidence: 99%